The Partnership between Traditional Birth Attendance (TBA) and Midwives in Childbirth Assistance: A Qualitative Study in East Manggarai Regency - Fransiska Nova Nanur; Ni Putu Widarini; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Partnership between traditional birth attendance (TBA) and midwives is one of the strategies to increase the coverage of childbirth assistance by the health personnel. This partnership seems to be ineffective as there were still TBA performed childbirth assistance. The study aims to find out about the overview and obstacles in the implementation of the partnership between TBA and midwives in the East Manggarai Regency. Methods: The qualitative research with in-depth interviews using open interview guide was conducted among 15 participants who were selected purposively, consisted of two village midwives, five TBAs who partnered with midwives, three TBAs who are not partnered with a midwife, and two participants of community leaders, the religious leaders, the two puerperal women and one policy maker. Data were analyzed by using thematic analysis approach. Results: The results showed that the facilities and supporting infrastructure of partnership were inadequate, funds provided were not enough to finance the implementation of the partnership, there were no regular meetings between the midwives and the traditional healers, coordination was done merely incidental. The division of roles in the treatment of childbirth was clear, but many obstacles were found, namely transportation barriers, economic problems and there were traditional healers who did not want to partner. Conclusion: The overview of partnership between the traditional healers and midwives in childbirth assistance has not gone well and there were still many obstacles found both internally and externally. To optimize this program, sufficient funds should be allocated, transportation should be improved and counseling should be provided to the community to raise awareness of the importance of childbirth assistance by the health personnel.